2016
DOI: 10.2134/agronj2016.02.0112
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Potato Growth and Nitrogen Uptake in Eastern Canada with the STICS Model

Abstract: The ability of process‐based soil–crop models to simulate potato (Solanum tuberosum L.) yield and N uptake for a range of N fertilization under the conditions of eastern Canada has never been tested. Our objectives were (i) to calibrate and evaluate the performance of the STICS model for the Shepody and Russet Burbank cultivars with cultivar‐specific critical N concentration dilution curves, and (ii) to quantify the gain in model performance with cultivar‐specific N concentration curves rather than a generic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…The normalized mean error (NME) (Equation ( 2)) estimates the model's relative bias. An |NME| < 10% is considered a low bias [40,62]. The normalized root mean square error (NRMSE) (Equation ( 3)) is used to determine the error of prediction of the model by giving more weight to larger errors and it represents the relative mean deviation of the predicted values to the observed values.…”
Section: Statistical Analysis and Model Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The normalized mean error (NME) (Equation ( 2)) estimates the model's relative bias. An |NME| < 10% is considered a low bias [40,62]. The normalized root mean square error (NRMSE) (Equation ( 3)) is used to determine the error of prediction of the model by giving more weight to larger errors and it represents the relative mean deviation of the predicted values to the observed values.…”
Section: Statistical Analysis and Model Evaluationmentioning
confidence: 99%
“…The verification of LAI dynamics which plays a key role in predicting plant biomass accumulation and the validation of the critical N dilution curve parameters for spring barley may also be required to predict AGB and NU more precisely. Morissette et al [40] concluded that using cultivar-specific N dilution curves instead of the default curve improves STICS performance and is essential for adequately predicting the N cycle of potato growing systems. To our knowledge, no critical N dilution curve for spring barley grown in agricultural soils from the six provinces of eastern Canada (New Brunswick, Newfoundland, Nova Scotia, Prince Edward Island, Quebec, and Ontario) has been established or at least validated to date.…”
Section: Suggestions To Improve Model Performancementioning
confidence: 99%
See 1 more Smart Citation
“…First, a general crop model can be made more specific by adjusting its parameters for different crops or cultivars (e.g. Morissette et al, 2016). It should be noted that this kind of procedure does not necessarily compromise the realism of the model.…”
Section: Applications Of Crop Models: An Overviewmentioning
confidence: 99%
“…Other applications of mechanistic potato models have been recently used in strategic planning, for testing different management options, and for scenario analysis. Morissette et al (2016) used the STICS model for the Shepody and Russet Burbank potato cultivars to generate cultivar-specific Critical Nitrogen Concentration Curves in eastern Canada. Borus et al (2016) used the new APSIMpotato model to simulate the effects of N-fertilizer levels, sowing dates, plant density and irrigation treatments, and tested the model in highly different climatic conditions (Tasmania and Kenya).…”
Section: Examples Of Recent Use Of the Models For Potato Productionmentioning
confidence: 99%